VD_FINDINFO HC / 2009 / 335 vom 21. Oktober 2009 - VD Tribunal cantonal (2009)
SUSPENSION DE LA PROCÉDURE, ACTION EN PARTAGE SUCCESSORAL, RAPPORT SUCCESSORAL, DROIT DES SUCCESSIONS | 123 al. 1 CPC, 124a CPC, 489 CPC, 567 al. 1 CPC, 567 CPC, 582 ch. 11 CPC, 586 al. 1 CPC, 586 CPC